Conventional and microwave-assisted organic synthesis of novel antimycobacterial agents bearing furan and pyridine hybrids - Desai, Nisheeth C.; Bhatt, Kandarp; Jadeja, Dharmpalsinh J.; Mehta, Harsh K.; Khedkar, Vijay M.; Sarkar, Dhiman (Drug Development Research, 2022)
Drug resistance in tuberculosis poses a serious threat to humanity because currently available antitubercular drugs are ineffective against Mycobacterium tuberculosis (M. tuberculosis). As a result, the approval of Bedaquiline and Delamanid for the treatment of drug-resistant tuberculosis was accelerated. Still, there is an urgent need to search for new antitubercular drugs with novel mechanisms of action (MoA). Due to this, we have designed a synthetic strategy by utilizing microwave-assisted organic synthesis. We have compared our method with the conventional procedure, and the data show that our procedure is more effective in the preparation of title compounds. A unique series of 1-(2-(furan-2-yl)-5-(pyridin-4-yl)-1,3,4-oxadiazol-3(2H)-yl)-3-(aryl)-pr op-2-en-1-ones (5a-o) was synthesized utilizing conventional and microwave-assisted techniques. Synthetic compounds were investigated for antitubercular activity against Mycobacterium TB H37Ra and Mycobacterium bovis (M. bovis). Compound 5b was reported to be the most effective against M. tuberculosis H37Ra (97.69 percent inhibition at 30 mu g/ml) and M. bovis (97.09 percent inhibition at 30 mu g/ml). An in silico binding affinity study of mycobacterial enoyl-acyl carrier protein reductase (InhA) reveals the binding mechanism and thermodynamic interactions that determine these molecule's binding affinity. Compound 5b had a high glide score of -8.991 and low glide energy of -49.893 kcal/mol.
Keywords: Antitubercular activity; microwave-assisted organic synthesis; Molecular docking